Impact of Luteinized Unruptured Follicles on Clinical Outcomes of Natural Cycles for Frozen/Thawed Blastocyst Transfer - Li, Song; Liu, Lokwan; Meng, Tian; Miao, Benyu; Sun, Mingna; Zhou, Canquan; Xu, Yanwen (Frontiers in Endocrinology, 2021)
Objective: To investigate the impact of luteinized unruptured follicles (LUF) on clinical outcomes of frozen/thawed embryo transfer (FET) of blastocysts. Methods: In this retrospective cohort study, 2192 patients who had undergone blastocyst FET treatment with natural cycles from October 2014 to September 2017 were included. Using propensity score matching, 177 patients diagnosed with LUF (LUF group) were matched with 354 ovulating patients (ovulation group). The LUF group was further stratified by the average LH peak level of 30 IU/L. Clinical pregnancy rate and live birth rate were retrospectively analyzed between the LUF and ovulation groups, as well as between LUF subgroups. Results: After propensity score matching, general characteristics were similar in the LUF and ovulation groups. Clinical pregnancy rate in the LUF group was significantly lower than that in the ovulation group (47.46% vs. 58.76% respectively, adjusted P = 0.01, OR 0.60, 95% CI 0.42–0.87). However, no significant difference was detected in live birth rate, although it was lower in the LUF group (43.50% vs. 50.00%, adjusted P = 0.19, OR 0.76, 95% CI 0.51–1.14). In the LUF subgroup analysis, both clinical pregnancy rate (43.02% vs. 62.30%, adjusted P = 0.02, OR 0.45, 95% CI 0.23–0.87) and live birth rate (37.21% vs. 59.02%, adjusted P = 0.01, OR 0.40, 95% CI 0.20–0.78) in the LH < 30 IU/L subgroup were significantly lower than those in the LH ≥30 IU/L subgroup. Conclusion: LUF negatively affected clinical outcomes of frozen/thawed embryo transfer of blastocysts, particularly when the LH surge was inadequate.